Pengaruh Subtitusi Cahaya Matahari dengan Lampu Led Terhadap Pertumbuhan Tanaman Padi (Oryza Sativa) Varietas IR 64 - Dewanto, Soni (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
Rice cultivating in a closed room requires artificial light to support the growth and yield of rice plants. The light provided by herus includes several factors including light intensity, length of exposure and light quality. This research aims to determine effect of the power LED lamp on the growth and yield of rice plants in the floating raft hydroponic cultivation system. This research used Randomized block Design with four treatments, namely: P0 (control/sunlight), P1 (LED lamp 100 watt), P2 (LED lamp 200 watt) and P3 (LED lamp 300 watt) which were repeated ten times. The parameters observed included plant height, number of plant saplings, wet stem weight, and dry stem weight. The treatment was carried out in boxes measuring 60 cm x 40 cm x 30 cm which were placed in 2 places, outdoors and in a dark room (indoors). The results showed that the control treatment (P0) gave the best results, with plant height (111.11 cm), number of plants saplungs (9 stems), wet stem weight (359.67 g), dry stem weight (64.74 g)